The Importance of Project Status for Career Success: A Network Perspective - Li, Shihan; Krackhardt, David; Niezink, Nynke M. D. (Journal of Management, 2026)
Employees’ career trajectories in project-based organizations are closely associated with their project participation history. Yet, little is known about what features make a project stand out as a career booster for its participants and who obtains more career benefits than others from working on “hotshot” projects. In this study, we focus on a unique feature of projects—project status—and theorize about potential network-related sources from which it derives. Specifically, we develop arguments for how the pattern of a project’s social relations with other projects in the project network reflects the project’s status. Then, we deduce hypotheses regarding the impact of project status on employees’ career advancement and the moderating role of one’s hierarchical level in this relationship, drawing on the literature on status diffusion, endorsement, evaluative uncertainty, and attribution. Our empirical examinations entailed two studies. Study 1 provides evidence for the validity of using a network structural feature of a project to indicate its status using data from a high-tech company’s R&D projects. Study 2 tested our hypotheses by leveraging a sample of over 1,000 IT specialists in a multinational accounting firm tracked over five years. We found that employees assigned to higher-status projects received faster promotions. This career advantage was moderated by a person’s organizational hierarchical level in a complex way such that middle-level people obtained more rapid promotions when assigned to high-status projects than their bottom- or top-level counterparts.